Bouchardatine analogue alleviates non‐alcoholic hepatic fatty liver disease/non‐alcoholic steatohepatitis in high‐fat fed mice by inhibiting ATP synthase activity. (4th July 2019) - Rao, Yong; Lu, Yu‐Ting; Li, Chan; Song, Qin‐Qin; Xu, Yao‐Hao; Xu, Zhao; Hu, Yu‐Tao; Yu, Hong; Gao, Lin; Gu, Lian‐Quan; Ye, Ji‐Ming; Huang, Zhi‐Shu
Abstract : Background and Purpose: Non‐alcoholic hepatic fatty liver disease (NAFLD) is a manifestation of the metabolic syndrome in the liver and non‐alcoholic steatohepatitis (NASH) represents its advanced stage. R17 derived from bouchardatine, shows benefits in the metabolic syndrome, but has not been tested in the liver. The present study examined the pharmacological effects of R17 in a model of NAFLD/NASH and its mode of action. Experimental Approach: The effects of R17 were examined in mice fed a high‐fat (HF) diet to induce the pathological characteristics of NAFLD/NASH and in cultures of HuH7 cells. We used histological and immunohistochemical techniques along with western blotting and siRNA. Generation of ROS and apoptosis were measured. Key Results: Administration of R17 (20 mg·kg −1, i.p. every other day) for 5 weeks reversed HF‐induced hepatic triglyceride content, inflammation (inflammatory cytokines and macrophage numbers), injury (hepatocyte ballooning and apoptosis, plasma levels of alanine aminotransferase and aspartate aminotransferase), and fibrogenesis (collagen deposition and mRNA expression of fibrosis markers). In cultured cells, R17 reduced cell steatosis from both lipogenesis and fatty acid influx. The attenuated inflammation and cell injury were associated with inhibition of both endoplasmic reticulum (ER) stress and oxidative stress. Notably, R17 activated the liver kinase B1‐AMP‐activated protein kinase (AMPK) pathway by inhibiting activity of ATP synthase, rather than direct stimulation of AMPK. Conclusion and Implications: R17 has therapeutic potential for NAFLD/NASH. Its mode of action involves the elimination of ER and oxidative stresses, possibly via activating the LKB1‐AMPK axis by inhibiting the activity of ATP synthase.